Initial treatment of patients with thyroid cancer: Outcomes and factors associated with care at academic versus nonacademic cancer centers. Issue 11 (15th January 2021) - Alhumaidi, Hebah; Manochakian, Rami; Cochuyt, Jordan; Chindris, Ana; Hodge, David; Abdulazeez, Mays F.; David, Shishir; Biswas, Suman; Aggarwal, Chander Shekher; Smallridge, Robert C.; Ailawadhi, Sikander
Abstract : Background: Factors associated with receiving initial care for thyroid cancer (TC) at academic centers (ACs) versus nonacademic centers (NACs) and their impact on patient outcomes have not been reported. Methods: The National Cancer Database with TC cases from 2004 to 2013 was evaluated for association of type of center for initial care with socioeconomic factors and disease and treatment characteristics, as well as overall survival (OS; all‐cause mortality). Results: The patients with TC (n = 200, 824) included were predominantly women (74%), non‐Hispanic Whites (85%), and from metro areas (84%). Sixty percent received initial care at a NAC. There were no significant differences between treatment groups by age or gender. Among those treated at an AC, a higher proportion belonged to racial/ethnic minorities (16.5%) versus at a NAC (11.6%). Hormone therapy was used more in an AC versus a NAC (60% vs 47%). Patients with all TC pathologies combined had a lower likelihood of death when they received initial care at an AC (hazard ratio [HR], 0.948; P = .0006). Among individual pathologic subtypes, a lower likelihood of death was noted when initial care was received at an AC for follicular (HR, 0.828, P = .0010) and Hurthle cell cancers (HR, 792; P = .0008), as well as stage II papillary thyroid cancer (HR, 0.828; P = .0026), but not for other histopathologic subtypes. Conclusions: Initial care at an AC was associated with lower likelihood of death for patients with TC, especially for those with follicular or Hurthle cell subtypes. Optimal resource use with consideration of patients' socioeconomic and demographic factors is imperative to ensure the most appropriate management of patients with TC in various treatment settings. Abstract : Initial care for patients with thyroid cancer at academic centers is associated with lower likelihood of death overall and for some of the specific pathologic subtypes. Although there are several socioeconomic, demographic, and clinical factors that probably contribute to this phenomenon, appropriate resource use in various treatment settings should be employed so patient outcomes can be optimized.